The ruptured bladder in the multiple trauma patient - Schneeberger, Federico; Cassinelli, Daniel; Bado, Alejandro; Ruiz Liard, Claudio (Cirugía del Uruguay, 1991)
Authors ana/yse retrospective/y a series of patients admitted to the Hospital de Clí nicas between Ju/y 1973 and December 1987 with vesical rupture as final diagnosis. The study refers to a total of 20 patients and is centered on 18 non-penetrating traumatisms. Age, sex, topography (extra or intraperitoneal or combined) are analysed. The frequency of associated lesions is pointed out.